Radiation Sterilization of Prototype Military Foods: Low-Temperature Irradiation of Codfish Cake, Corned Beef, and Pork Sausage - Anellis, Abe (1972)
“Screening” packs comprising 10 lots each of codfish cake, corned beef, and pork sausage, each lot containing about 10(6) spores of a different strain (five type A and five type B) of Clostridium botulinum per can, were irradiated at −30 ± 10 C with a series of increasing doses (20 replicate cans/dose) of (60)Co gamma rays. The cans were incubated for 3 months at 30 C and examined for swelling, toxin, and recoverable botulinal cells. Based on the latter criterion of spoilage, median lethal dose (LD(50)) and D values were estimated for each strain in each food. The most resistant strain in codfish cake, corned beef, and pork sausage was, respectively, 53B, 77A, and 41B. There was no clear-cut trend in the comparative order of resistance between the two antigenic types among the three foods. LD(50) values gave essentially the same order of resistances as the D values and may be used interchangeably with the latter for the 10 test organisms. “Clearance” packs consisting of the most resistant strain (about 10(7) spores/can) with its respective food were irradiated with a variety of doses at −30 ± 10 C, using 100 replicate cans/dose (about 10(9) spores/dose). These packs were incubated for 6 months at 30 C and assayed for the three types of spoilage. Based on recoverable cells, the experimental sterilizing doses (ESD) for codfish cake, corned beef, and pork sausage were 2.5< ESD ≤ 3.0, 2.0 < ESD ≤ 2.5, and 1.5 < ESD ≤ 2.0 Mrad, in that order. Assuming exponential spore death, the 12D values, or minimal radiation doses (MRD), were 3.24, 2.44, and 2.65 Mrad, respectively. Estimation of the MRD values by a method which assumes that spore death in the cans follows a normal distribution, yielded 3.09, 2.57, and 2.39 Mrad, respectively. Weibull analyis of the pooled 10-strain viable cell spoilage data of the screening packs for codfish cake or corned beef suggested that spore death in the cans follows a normal distribution yielded 3.09, 2.57, pooled data were not amenable to such analysis. Sublethal doses (0.5, 0.75 Mrad) increased the visible spoilage rate of corned beef over that of unirradiated controls. Apparently radiation-injured spores of C. botulinum were sensitized to the presence of food additives such as curing salts, NaCl, and spices.